Screening colonoscopy in HIV‐infected patients: high rates of mucosal abnormalities in a German HIV‐infected cohort. Issue 3 (16th October 2013) - Kasapovic, A; Boesecke, C; Schwarze‐Zander, C; Anadol, E; Vogel, M; Hippe, V; Schmitz, V; Rockstroh, JK; Wasmuth, JC
<x xml:space="preserve">Abstract</x> Objectives Because of the improved life expectancy provided by successful antiretroviral combination therapy, preventive health measures in HIV‐infected patients have assumed increasing importance. To date, no data exist on rates of mucosal abnormalities detected by screening colonoscopy in > 50‐year‐old HIV‐infected patients in Germany. The aim of this study was to obtain such data. Methods A screening colonoscopy was offered to 159 HIV‐infected patients (age > 50 years) who presented for HIV standard of care visits at the infectious diseases out‐patient clinic at the university hospital in Bonn over a 1‐year period from February 2010. Pearson's χ2 test, Fisher's exact test and the Mann−Whitney U‐test were used for statistical analysis. Results Fifty‐one patients (32.1%) had undergone a screening colonoscopy in the past 10 years, and 45 patients (28.3%) were eventually screened in the observation period. The median age of the 96 screened patients (86% male and 14% female) was 58 years [interquartile range (IQR) 54–64 years]. Overall, endoscopic abnormalities were found in 61% of patients. Histological examination showed tubular adenomas in 21.9% of patients, tubulovillous adenomas in 3.1% and serrated adenomas in 1%. Hyperplastic polyps were found in 15.6% of patients, a nonspecific colitis in 16.7% and diverticulosis in 12.5%. In four cases there was even an early‐stage carcinoma (two anal, one rectal and one colon cancer). In univariate analysis, no significant differences with regard to immune status, highly active antiretroviral therapy, family history, personal risk factors or comedication were found between patients with dysplastic and normal mucosas. Conclusions The high acceptance rate of screening colonoscopy and the in comparison with the HIV‐negative population comparably higher rate of abnormalities in this cohort of HIV‐infected patients justify enhanced implementation of screening colonoscopy in clinical practice.